Pendampingan Pencatatan Keuangan Sederhana Bagi Pelaku UMKM Bidang Pariwisata di Desa Petahunan, Kab. Banyumas - Aning Fitriana; Reza Rahmadi Hasibuan; Karunia Zuraidaning Tyas; Dyah Supriatin (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
Micro, Small, and Medium Entreprisess are businesses run by commoner with limited capital, and apply simple technology. Micro, Small, and Medium Enterprises are an important part of the country's economy so it needs the role of the government to be able to support the existence of MSMEs. But the challenges faced by MSMEs are not easy such as making simple financial statements so that later they can be used as a condition for credit applications at banks, this is done so that MSMEs continue to grow and can innovate. The purpose of this activity is that business actors/MSMEs in Petahunan  can apply continuously to simple financial records on each transaction. Methods carried out by counseling, training and mediation, as well as direct practice regarding recording transactions. The results showed that the participants enthusiastically participated in counseling, actively asking to be able to make financial statements simply.  Based on this activity, it can be concluded that the MSMEs of petahunan  have understood the importance of recording transactions to make simple financial statements. This will certainly have a good impact on business continuity and to create economic independence.